Microplastic accumulation in a Zostera marina L. bed at Deerness Sound, Orkney, Scotland. (March 2020) - Jones, Katherine L.; Hartl, Mark G.J.; Bell, Michael C.; Capper, Angela
Abstract: Seagrasses have global distribution and are highly productive and economically valuable habitats. They are sensitive and vulnerable to a range of human-induced pressures, including ongoing exposure to marine litter, such as microplastic particles (<5 mm). In this study, a Zostera marina bed in Deerness Sound, Orkney was selected to determine whether microplastics accumulate in seagrass beds and adhere to seagrass blades. Sediment, seagrass blade, biota and seawater samples were collected. 280 microplastic particles (0.04 to 3.95 mm (mean = 0.95 mm ± 0.05 SE)) were observed in 94% of samples collected ( n  = 111). These were visually categorised into type (fibre, flake, fragment) and colour, and 50 were successfully identified as plastic using ATR-FTIR. Fibres contributed >50% of the total microplastics observed across all samples. This is the first known study on Z. marina to describe microplastic loading within a seagrass bed and to identify microplastic adherence to seagrass blades. Highlights: Z. marina seagrass beds act as a sink for microplastics with higher loadings than bare sandy sediment sites. First known observation of microplastics adhering to Z. marina blades. Microplastic identified in sediment, on seagrass blades, in associated biota and in seawater samples. Fibres contributed >50% of the total microplastics observed. Of the 50 samples analysed by ATR-FTIR, poly(ethylene) was recorded as the most common (34%).